USING POWTOON TO DEVELOP ANIMATED LEARNING VIDEO FOR TEACHING SPEAKING - Rahmadhani, Astuti Pratiwi; Miladiyenti, Fithratul (TELL - US JOURNAL, 2023)
As the pandemic Covid-19, all teaching learning process must be presented through online learning. Therefore, the teaching learning media also must be developed to support the process. Powtoon is a web-based application which allows the users to create an animated video. This study reports on the development of animated learning video using Powtoon for Speaking subject. The study employed an ADDIE research method which is started from Analysis, Design, Development, Implementation, and Evaluation. The result shows that Powtoon as web-based application for creating animated video has many features in making an animated video help to produce an interesting video for students